Anonymous

What Is 4(1.5c + 6) - 2c = -9?

3 Answers

Anonymous Profile
Anonymous answered
4(1.5c + 6) - 2c = -9

Ok, so the first thing you do, by the rules of PEMDAS (Parenthesis, Exponents, Multiplication, Division, Addition, Subtraction), is to distribute the parenthesis. To do this, you multiply the four to 1.5c and to 6.

(6c + 24) - 2c = -9

The next thing you do after that is combine the like terms, so first you should combine the numbers with the c variable.

6c - 2c + 24 = -9
4c + 24 = -9

Now, after you combined those, you now combine the numbers. There are several ways to do this, but there is an easy way to do it. First you need to let the variable stay at one side of the equation. So, you shall subtract 24 from both sides.

(4c + 24) - 24 = -9 - 24

4c = -33

After you have done that, divide both of the sides by four, which will leave you the answer to c.

4c/4 = -33/4
c = -8.75

That is your final answer. The previous poster who has gotten c = 3.75 got it wrong, the calculations I have posted on this post are the correct calculations. Use a calculator if you want :P.
Oddman Profile
Oddman answered
4(1.5c + 6) - 2c = -9 6c + 24 - 2c = -9    (use the distributive property to eliminate parentheses) 4c = -33    (subtract 24, collect terms) c = -33/4    (divide by 4) c = -8 1/4    (convert to a mixed number. The decimal equivalent is -8.25.) 
Check   4(1.5(-8 1/4) + 6) - 2(-8 1/4) = -9    (substitute for c)   4(-12 3/8 + 6) + 16 1/2 = -9   4(-6 3/8) + 16 1/2 = -9   -25 1/2 + 16 1/2 = -9    (yes)
Anonymous Profile
Anonymous answered
4(1.5c + 6) - 2c = -9

First, distribute the 4 to the 1.5c and the 6.

6c + 24 - 2c = -9

4c + 24 = -9

4c = 15

c = 3.75

Hope this helps

Answer Question

Anonymous